The SmartAG partner: CCAFS East Africa quarterly newsletter, April–June 2013 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
In this issue, we focus on CCAFS East Africa work in Tanzania and Uganda, on integrating farmers’ indigenous technical knowledge with scientific weather information. We also highlight ongoing work with farmers to find innovative climate smart practices that will improve their capacity to adapt to climate change and manage risks. On policy, we are continuing to work with East African partners to ensure that agriculture is reflected in the climate change policy discussions.